PELAKSANAAN PEMBERIAN KREDIT DI KOPERASI SIMPAN PINJAM (KSP) - Paulus Paulus (Universitas Kapuas Sintang, 2024)
This research method is descriptive qualitative. Data collection techniques include interviews, documentation and observation. Informants (subjects) of research using Proposive sampling and Accidental Sampling methods. The scope of this research is the Implementation of Credit Provision with the aspects used in the research, namely: 1) Credit Administration, 2) Credit Analysis, 3) Credit Supervision, 4) Member Development. This research was carried out at KSP CU Tri Tapang Kasih, Sejiram District, Kapuas Hulu Regency. Loan administration takes the form of governance carried out by the credit department in the credit management process. This governance takes the form of procedures that must be carried out and documents that must be owned and filled out when applications, agreements and loan disbursement occur. The KSP CU Tri Tapang Kasih institution has carried out administration well based on credit governance. Credit analysis is guided by the 5 C Analysis (Character, Capacity, Capital, Collateral, and Condition). Credit supervision includes monitoring the use of credit by members, implementation of installment payments, as well as credit administration. Implementation has gone well. Coaching for members takes the form of providing motivation and education for members. The implementation of coaching is in accordance with the work program and is going well.